PENGARUH PERILAKU BIROKRASI TERHADAP KUALITAS LAYANAN PUBLIK PADA DISTRIK SEMANGGA - Samuel Atbar (SOCIETAS, 2012)
This study aims to determine and measure how much influence bureaucratic behavior on the quality of public services in the District Semangga. each variable is described in four-dimensional indicators and three. The research method used is a quantitative analysis of the survey method using questionnaires as the main instrument. Quantitative data processing system using a statistical dioleh Product and Service Solutions (SPSS. 17.0) The results showed that the statistical behavior of the bureaucracy affects the quality of public services in the District with Semangga 0.5 can also be proved by comparing the values of r calculated with the table r (95%) so that the table r = 0.138. Since r count r is greater than the table or 0.519>0.138 then conclude that Ho is rejected and Ha accepted, meaning that the behavior of the bureaucratic behavior has a significant effect on the quality of public services in the district of Merauke regency SemanggaThis study aims to determine and measure how much influence bureaucratic behavior on the quality of public services in the District Semangga. each variable is described in four-dimensional indicators and three. The research method used is a quantitative analysis of the survey method using questionnaires as the main instrument. Quantitative data processing system using a statistical dioleh Product and Service Solutions (SPSS. 17.0) The results showed that the statistical behavior of the bureaucracy affects the quality of public services in the District with Semangga 0.5 can also be proved by comparing the values of r calculated with the table r (95%) so that the table r = 0.138. Since r count r is greater than the table or 0.519>0.138 then conclude that Ho is rejected and Ha accepted, meaning that the behavior of the bureaucratic behavior has a significant effect on the quality of public services in the district of Merauke regency Semangga